Wittgenstein's lasting significance - Kölbel, Max; Weiss, Bernhard (Routledge, 2004)
Ludwig Wittgenstein (1889-1951) has exerted a more powerful influence on contemporary philosophy than any other twentieth-century thinker. But what is the nature of this influence and why has it proved so enduring?In Wittgenstein's Lasting Significance, twelve contemporary philosophers explore the issues surrounding Wittgenstein's importance and relevance to modern thought. Their articles, all of which are published here for the first time, cover the entirety of Wittgenstein's major publications: the Tracatus Logico-Philosophicus, Philosophical Investigations.